Optimisation of microwave-assisted extraction (MAE) of anthraquinone and flavonoids from Senna alata (L.) Roxb - Yeong, Yi Ling; Pang, Sook Fun; Putranto, Aditya; Jolius, Gimbun (Taylor & Francis, 2021)
AbstractThis paper investigates the optimum processing conditions of microwave assisted extraction (MAE) of anthraquinone (aloe emodin, AE) and flavonoids (kaempferol 3-gentiobioside, K3G and kaempferol, KA) from Senna alata (L.) Roxb. The kinetic study indicates that MAE showed a greater extraction rate, compared to ultrasonic-assisted and maceration, due to the enhanced power which altered the leaf microstructures. The optimisation was undertaken using one-factor-at-a-time, two-level factorial design and central composite design were used to maximise the yield of the target compounds. The optimum yield of K3G (4.27 mg/g DW), KA (8.54 mg/g DW) and AE (0.86 mg/g DW) was obtained at 90.5% ethanol, microwave power of 18.6 W/mL with a desirability of 0.82. In addition, the yield of K3G and KA is correlated positively with the antioxidant activity.